Minimally Invasive Mitral Valve Surgery for Mitral Valve Infective Endocarditis - Folkmann, Sandra; Seeburger, Joerg; Garbade, Jens; Schon, Uta; Misfeld, Martin; Mohr, Friedrich W.; Pfannmueller, Bettina (The Thoracic and Cardiovascular Surgeon, 2018)
Background The feasibility of minimally invasive mitral valve (MV) surgery in infective endocarditis (IE) has not been reported in detail. We assessed the safety, efficacy, and durability of the minimally invasive approach through a right anterolateral minithoracotomy for surgical treatment of MV IE.Methods A review of the Leipzig Heart Center database revealed 92 eligible patients operated on between 2002 and 2013. All patients had undergone minimally invasive surgery for IE. The indication for surgery was isolated IE of the MV in all patients. Baseline and intraoperative data, as well as clinical outcomes and short-term follow-up were analyzed retrospectively.Results The patients' mean age was 60.9 ±  15.3 years, the logistic EuroSCORE II was 19.6 ± 19.1%, and 64.1% (59) were male. MV repair was feasible in 23.9% (22/92) of patients. Repair techniques included annuloplasty ring implantation, anterior mitral leaflet resection, posterior mitral leaflet resection, and implantation of neochordae. MV replacement was performed in 69 patients (75%), a mitral annulus patch in 1 patient, and concomitant tricuspid valve surgery for tricuspid regurgitation in 5 patients. Bacteriological analysis showed staphylococcus infection in 45.5%, streptococcus in 36.4%, enterococcus in 13.6%, and others in 4.5%. The 30-day-mortality rate was 9.8% (9 patients). The 1-year follow-up showed a 1-year survival rate of 77.7 ± 4.4% and freedom from reoperation within 1 year due to reendocarditis of 93.3 ± 2.1%.Conclusions The minimally invasive approach is suitable for the treatment of IE of the MV. It is a good technique in IE in selected patients.
Keywords: minimally invasive; mitral valve; endocarditis